Study Of Fat Reduction On Catfish (Pangasius Hypophthalmus) Surimi Which Prepared Submerged Methods - Saipul Anwar; Suparmi '; Sumarto ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was intended to evaluated fat concentration of catfish surimi prepared by different washing methods. Catfish were teken from fish pond culture in Pekanbaru. The fish were filleted, ground and the mince was grouped into three parts which washed respectively in cold water without salt, cold water + 0,3% saltfor 30 minutes and without soaking. The fish then was pressed; and the surimi was evaluated for fat, protein, TVB, pH and yield. The result showed that the fat of surimi washed in cold water without salt has the best quality. Fat concentration for the surimi washed in cold water without salt, cold water + 0,3% salt and without washing was 5,138%, 5,794%, 6,454% respectively. Protein TVB, pH and yield for surimi washed in cold water without salt were 14,186%, 11,52 mgN/100g, 6,798 and 25,01% respectively; for surimi washed in cold water + 0,3% salt were 13,93%, 9,28 mgN/100g, 6,848 and 23,17% respectively; and for surimi without washed were 15,846%, 16,64 mgN/100g, 6,848 and 28,72% respectively.Keywords: Surimi, Fat, Reduction, Cold water, Salt